Civic engagement and higher education: The 2014 elections and the political behavior of Brazilians - Dias, André Luiz Vieira [UNESP] (2017)
The objective of this chapter is to analyze the influence of the variable schooling on the political behavior of Brazilians. It starts from the assumption that this is an independent variable capable of awakening a more interested, participatory and coherent behavior, therefore, engaged citizens. In this sense, we seek to verify that Brazilian citizens are informed and interested in politics; motivated to participate in elections and other political activities; and their assessment and satisfaction with the democratic process. In particular, there is the behavior of those who have completed higher education, compared to other levels of education in order to identify distinct behavioral patterns. From the data obtained by ESEB 2014 and descriptive analysis of the data, we applied the logistic regression model relating the variable schooling and other variables grouped into four categories: a) socioeconomic aspects; b) information and interest in politics; c) participation in the elections, in traditional and nontraditional political activities; and d) evaluation and political satisfaction. Among the most educated, we have predominance of women, a younger audience and with family income subtly than the less educated. They tend to behave differently: they are slightly more informed and interested in politics; despite the low percentages found, they are the ones that participate in political activities in general; they are the ones who support democracy, but the most dissatisfied with their operation. This study allows us to understand the behavior patterns of Brazilians and, more specifically, the most educated, poorly studied by political science in Brazil.